A Study on the Parental Awareness on the Heavy Weight School Bag of Primary School Children in Guwahati City - Das , Dipjyoti (International Journal of Psychosocial Rehabilitation, 2020)
Children’s in many countries including India have to carry a huge load on their back to fulfill the present demand of academic carrier which has so many ill effect on the child’s physical and mental health. The present study wants to throw lights on the parental awareness on the heavy weight schoolbag and also to find if there is any relationship between the educational level of the parents and their awareness towards the school bag load. The study was conducted under descriptive survey method where 100 samples of parents were collected through convenient sampling. Data were analyzed through simple percentage, Chi square and Contingency coefficient to see the relationship.